Digital technologies and healthcare architects' wellbeing in the National Health Service Estate of England during the pandemic - Chrysikou, Evangelia; Papadonikolaki, Eleni; Savvopoulou, Eleftheria; Tsiantou, Eleni; Klinke, Christian Alexander (Frontiers in Medical Technology, 2023)
UK Built Environment is currently undergoing a digital transformation, as is happening in the National Health Service (NHS) of England. In this paper the focus was on the intersection of the two sectors and specifically the potential digital transformation of the NHS Estate. The NHS has developed a strategy for its workforce, to improve staff health and wellbeing, support equality, diversity, inclusion and the development of existing staff. Digital technologies (DTs) could relate to all Estates and Facilities Management priorities as it crosscuts all proposed actions. As opposed to most studies on the wellbeing of blue-collar workers, the team focus on white-collar workers and specifically the architects working in the NHS, especially since NHS at this stage is developing two important policies: the new hospital programme and the workforce action plan. Therefore, it is important for the NHS to look at the digital transformation strategy in the prism of the other two. As architecture has a traditionally low job satisfaction, it negatively impacts wellbeing. This research argues that this might have been accentuated during the pandemic for the architects working in the NHS and dealing with the added pressure from three new major tasks: adjusting infrastructure capacity for fighting Covid-19 and creating the infrastructure for the testing and vaccination programs. DTs in architecture potentially affect job satisfaction in terms of creativity, autonomy, time pressure, organisational commitment etc. Methodology comprises literature review and a pilot of interviews with healthcare architects/designers working in the NHS or on NHS related projects. The research context is informed by the Covid-19 crisis that brought healthcare architecture to the frontline of the pandemic with NHS architects creating new wards and vaccination centers, while private healthcare architects designed new hospitals. In the niche area of healthcare architecture, architects were in their busiest year. Yet, the DTs available to them currently could only support limited tasks and did not link well to operational data. To explore how DTs transform the wellbeing of healthcare architects. Understanding wellbeing in healthcare architecture in light of digital transformation is crucial for creating the necessary leadership for the sector to grow.